THE EFFECT OF USING THE SCRATCH MEDIA ON THE CREATIVE SKILLS OF IPS LEARNING - Age Larasati, Diyas; Roosyanti, Anna (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2026)
This study aims to find out how using the Scratch media affects students' creative skills in Social Studies (IPS) learning at SDN Bangsal. This is based on the need for interactive learning media that can stimulate students' imagination, problem-solving abilities, and creative expression. The research method used is a quasi-experimental design with a pretest-posttest control group. The subjects are fifth-grade students at SDN Bangsal, divided into an experimental group and a control group. The research instruments include a creativity skills observation sheet and a learning outcome test. The results show that using Scratch media has a positive and significant impact on improving students' creative skills, especially in terms of fluency, flexibility, originality, and elaboration. Students who learn with Scratch media are better able to develop ideas, express IPS concepts through animations, and create creative solutions to social issues studied. Therefore, Scratch media is effectively used as an innovation in IPS learning at the elementary level to maximize students' creative skills.